Playing Atari with Saddam Hussein : based on a true story - Roy, Jennifer Rozines, 1967-; Fadhil, Ali (Houghton Mifflin Harcourt, 2018)
For forty-two days in 1991, eleven-year-old Ali Fadhil and his family struggle to survive as Basra, Iraq, is bombed by the United States and its allies.